The Impact of Transformational Leadership and Organizational Culture on Employee Performance: Case Study in A Furniture Company - Rizki, Dwiki Fatur (Dinasti Publisher, 2024)
This research examines the impact of transformational leadership and organizational culture on furniture industry employee performance, focusing on CV. Agung Jaya Putra Furniture. The decline in employee performance from September 2023 to January 2024 is a significant concern. Using a narrative qualitative approach, this research examines the influence of leadership and organizational culture on employee performance through semi-structured interviews, direct observation, and document analysis from various levels of management and employees. The results show that transformational leadership and positive organizational culture significantly affect employee performance. Transformational leadership, which involves ideal influence, inspirational motivation, intellectual stimulation, and individualized consideration, creates a motivating work environment. In addition, an organizational culture that supports collaboration, innovation, and recognition also plays a vital role in improving employee performance. Job satisfaction mediates between leadership style, organizational culture, and employee performance. Research recommendations include developing leadership training programs, maintaining a positive organizational culture, attention to factors influencing job satisfaction, adopting flexible management approaches, and integrating transformational leadership values and organizational culture into daily management practices. These findings provide valuable insights for human resource management practitioners and organizational leaders to improve employee performance and long-term business success in the furniture industry. Implementing effective leadership strategies and developing a positive organizational culture is critical to achieving optimal employee performance and overall company success